Monetary Transmission of State Emerging MarketsLine Asset Prices: Inflation Control Leading Indicators - Rusiadi (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
This study examines the problem of transmission that does not cause the final goal of the policy is not achieved. The target is to determine the leading indicator of the most dominant variable in controlling inflation in emerging market countries. Data analysis using Vector Autoregression. The result of the study states the Effectiveness of policy recommendations in the short-term policy to control inflation is by increasing investment and consumption. The effectiveness of the policy recommendation of medium-term control policy to control inflation is recommended with increased investment and interest. The effectiveness of long-term recommendation of control policy is recommended by investment and money supply.